Modelling of multi-mitigation strategies for maritime disruptions in the wheat supply chain - Gurning, Saut (Strojniški vestnik, 2013)
This paper assesses the potential mitigation strategies for maritime disruptions occurring during the containerised transport of wheat in wheat supply chains (WSC). The assessment focuses on four major mitigation strategies (inventory and sourcing mitigation, contingency rerouting, recovery planning, and business continuity planning) to determine their suitability for managing potential disruptions in the WSC. In this paper, a Markovian-based methodology is the prime means used to evaluate the WSC mitigation strategies. The results of the continuous time period of the Markov chain application recommends that optimised mitigation strategies include the measurement and prediction of WSC costs and time functions during a one year period.
Keywords: containerised chains; kontejnerske verige; maritime disruptions; motnje v pomorskem delu; multi-mitigation strategies modeling; oskrbe s pšenico; večtirne strategije blažitve posledic; wheat supply